Doctor Who : the animation collection [videorecording (DVD)]. - Adams, Douglas, 1952-2001; Roberts, Pennant; Ford, Phil; Russell, Gary; Barnes, Alan, 1970-; Cornell, Paul; Milam, Wilson; Whitaker, David, 1928-1980; Barry, Christopher, 1925-2014 (BBC, 2019)
Five Doctor stories with original voice actors use animation to fill in the gaps of lost episodes with original soundtracks and scripts.